(untitled) (Annals of Medical Research, 2023)
Aim: Workers in the textile industry commonly use their upper extremities, and neck while working. The prevalence of neck and arm pain among workers in the textile industry is well understood. Impaired cervical lordosis is associated with pain and functional disability. Scientific studies have rarely focused on anatomical foundations. Our aim of the study is to measure the cervical lordosis angles (Cobb C2-7) of workers working in the textile industry. Materials and Methods: Our study is a single-center, non-randomized, retrospective, and observational. Demographic information, clinical and radiological images were analyzed hospital records. Recorded visual analog scale, neck pain, arm pain, and sensory problems were examined hospital records. “Cobb 2-7” angles were measured by a single physician with the program called “Akgün”, which is the electronic database program used by the hospital. Results: We detected a total of 53 textile workers. 33 (62,26%) were female and 20 (37,73%) were male. All of the cases gave a history of working position with their neck flexion. The demographic information of the patients is shown in the table. The average of the Cobb 2-7 angles of the cases was measured as -6.43±12.17. Conclusion: Textile workers commonly have neck pain. we detected deterioration in the cervical alignment of textile workers. We attribute the cause of neck pain in textile workers to the flexion position of the neck. We think that the continuous neck flexion position impairs cervical lordosis. Further prospective and high-quality studies are needed.